2017
DOI: 10.1111/cdev.12745
|View full text |Cite
|
Sign up to set email alerts
|

Age of Bilingual Exposure Is Related to the Contribution of Phonological and Semantic Knowledge to Successful Reading Development

Abstract: Bilingual children's reading as a function of age of first bilingual language exposure (AoE) was examined. Bilingual (varied AoE) and monolingual children (N = 421) were compared in their English language and reading abilities (6-10 years) using phonological awareness, semantic knowledge, and reading tasks. Structural equation modeling was applied to determine how bilingual AoE predicts reading outcomes. Early exposed bilinguals outperformed monolinguals on phonological awareness and word reading. Phonology an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 80 publications
(115 reference statements)
4
54
0
4
Order By: Relevance
“…It has long been recognized that deaf children's receptive and expressive ASL abilities are predictive of reading achievement [4,7,60,101,[121][122][123][124][125][126][127][128][129][130][131]. Additionally, recent neuroimaging research has produced evidence that bilingualism, regardless of language modality, yields language-specific plasticity in the brain's left hemisphere that supports later literacy development [132][133][134]. Taken together, these research findings have led Humphries et al [59] to argue that "the cognitive factor that correlates best to literacy among deaf children is a foundation in a first language" (p. 39).…”
Section: Sign Language As a Foundation For Literacymentioning
confidence: 99%
“…It has long been recognized that deaf children's receptive and expressive ASL abilities are predictive of reading achievement [4,7,60,101,[121][122][123][124][125][126][127][128][129][130][131]. Additionally, recent neuroimaging research has produced evidence that bilingualism, regardless of language modality, yields language-specific plasticity in the brain's left hemisphere that supports later literacy development [132][133][134]. Taken together, these research findings have led Humphries et al [59] to argue that "the cognitive factor that correlates best to literacy among deaf children is a foundation in a first language" (p. 39).…”
Section: Sign Language As a Foundation For Literacymentioning
confidence: 99%
“…Bilingual children learning to read in a second language face the additional challenge of mapping letters to sounds in not one, but two phonological and writing systems as compared to their monolingual peers. Multiple studies of different populations have found differences between monolingual and bilingual children's phonological awareness abilities, findings that have important theoretical implications for reading development given the key role of phonological awareness in reading (Berens, Kovelman, & Petitto, ; Eviatar & Ibrahim, ; Jasińska & Petitto, ; Kovelman, Baker, & Petitto, ; Rubin & Turner, ). Children educated in bilingual English–Spanish schools were found to outperform children from monolingual English schools on measures of phonological awareness (Kovelman et al, ) and word reading and passage comprehension (Berens et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Children educated in bilingual English–Spanish schools were found to outperform children from monolingual English schools on measures of phonological awareness (Kovelman et al, ) and word reading and passage comprehension (Berens et al, ). Similarly, English‐speaking children attending French immersion schools also demonstrated advantages in phonological tasks (Jasińska & Petitto, ; Rubin & Turner, ). Children who grow up speaking two languages, from a sample of diverse language pairings, including English, also demonstrated higher performance on phonological awareness and nonword reading tasks compared to English monolingual children attending the same school (Jasińska & Petitto, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations